The Effect of Work Motivation and Work Discipline on Employee Performance Through Work Procedures As Intervening Variables - Yeni Puspitasari; Nazaruddin Malik; Uci Yuliati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the effect of work motivation and work discipline on employee performance through work procedures as an intervening variable. The type of data used in this study is associative using quantitative research methods. The population of this study was 83 respondents with a total sampling method. The data analysis technique uses path analysis. The results show that work motivation has a positive and significant effect on employee performance, work discipline has a positive and insignificant effect on employee performance, and work motivation has a positive and insignificant effect on employee performance. The results of the F test show that work motivation, work discipline, and work procedures together affect employee performance.